Reconnaissance map of Seward Peninsula, Alaska / compiled by Alaskan Branch, Department of the Interior, U.S. Geological Survey - Geological Survey (U.S.) Alaskan Branch (Geological Survey, 1935)
Relief shown by contours and spot heights. "Reprinted 1935." "Surveyed in 1900, 1901, 1903, 1904, 1905, 1909." "Portions of the shoreline and geodetic positions based upon data by U.S. Coast and Geodetic Survey." Color 1:500,000